1990
DOI: 10.1152/ajpgi.1990.259.3.g340
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in regenerating and acute-phase rat liver

Abstract: The integration of growth and the acute-phase response is investigated by comparing the mRNA levels in rat liver during acute inflammation with those after partial hepatectomy. Northern analysis is carried out for the mRNAs for thiostatin, alpha 2-macroglobulin, alpha 1-antitrypsin, inter-alpha-trypsin inhibitor subunit 1, haptoglobin, ceruloplasmin, transferrin, vitamin D-binding protein, alpha 1-acid glycoprotein, beta-fibrinogen, apolipoproteins A-IV and E, albumin, transthyretin, alpha 2-HS-glycoprotein, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
75
0
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 32 publications
10
75
0
1
Order By: Relevance
“…A time-course study of these hepatic mRNA levels following a TO challenge is shown in Figure 3. The fetuin-A mRNA level was transiently down-regulated as expected from former reports [23,36] while the mRNA level for a positive APP used as a control, namely the IαIH4P protein of the Inter-α-Inhibitor family, was transiently up-regulated as described previously [37]. The level of fetuin-B mRNA was down-regulated as early as 9 h post-TO, reached a 2-fold decrease at days 1-2 and returned to a normal value beyond 1 week, which on the whole is similar to the variations seen for the fetuin-A mRNA level.…”
Section: Inflammation-associated Changes In Hepatic Level Of Fetuin-bsupporting
confidence: 82%
See 1 more Smart Citation
“…A time-course study of these hepatic mRNA levels following a TO challenge is shown in Figure 3. The fetuin-A mRNA level was transiently down-regulated as expected from former reports [23,36] while the mRNA level for a positive APP used as a control, namely the IαIH4P protein of the Inter-α-Inhibitor family, was transiently up-regulated as described previously [37]. The level of fetuin-B mRNA was down-regulated as early as 9 h post-TO, reached a 2-fold decrease at days 1-2 and returned to a normal value beyond 1 week, which on the whole is similar to the variations seen for the fetuin-A mRNA level.…”
Section: Inflammation-associated Changes In Hepatic Level Of Fetuin-bsupporting
confidence: 82%
“…In all groups, total hepatic RNAs from five animals were pooled, separated by electrophoresis, blotted and successively hybridized with four rat cDNA probes, namely those for (i) fetuin-A, (ii) fetuin-B, (iii) IαIH4P used herein as a control for a positive APP mRNA [28,37] and (iv) GAPDH used as a control for an mRNA whose level does not vary in liver during APR [36,37]. A single blot was used throughout the study.…”
Section: Table 1 Hepatic Levels Of Fetuin-a and Fetuin-b Mrnas As A Fmentioning
confidence: 99%
“…117,118 In the Swiss study, 106 although indices of inflammation were increased in the obese children, they were not correlated with RBP4, suggesting that subclinical inflammation is not a confounder in this age group. These data differ from those of Balagopal et al,116 in which CRP is correlated with RBP4 in adolescents, a difference that may have been owing to differences in age and/or pubertal stage.…”
Section: S13mentioning
confidence: 83%
“…Although RBP4 is a negative acute-phase protein, 117 nearly all earlier studies did not assess the potential confounding of RBP4 by subclinical inflammation, a common finding in obesity. 117,118 In the Swiss study, 106 although indices of inflammation were increased in the obese children, they were not correlated with RBP4, suggesting that subclinical inflammation is not a confounder in this age group.…”
Section: Retinol-binding Proteinmentioning
confidence: 99%
“…This model has also been used to analyse the expression of hepatic genes during different phases of the cell cycle. It has been shown that transferrin mRNA is detectable very late in the regenerating liver, and thus it belongs to the set of delayed genes of the cell cycle [5]. The transferrin gene is therefore probably regulated in part by immediate-early genes.…”
Section: Introductionmentioning
confidence: 99%